Neuroma of the Hand in Basketball Player: A Case Report - Jonathan, Harry; Budiharsana, Meiwita (Universitas Negeri Semarang, 2021)
Traumatic neuroma is a non-neoplastic overgrowth of axons and Schwann cells at the proximal site of nerve disruption as a form of thwarted axonal regeneration. It is growing from a severed, partially resected, or injured nerve as a result of trauma or surgery. Traumatic neuroma of the hand is a rare disorder; it was first reported in the medical literature as early as 1811 when Odier described “nerve tumors” which develop at the site of nerve transaction. We reported a twenty-two-year old male patient suffered from a traumatic neuroma of the hand due to basketball injury, who diagnosed by clinical examination and plain X-ray. The patient was treated by surgical excision of the neuroma, and patients could return to competitive sport on the fourth months after surgical treatment.